2007
DOI: 10.1021/es062757h
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Colloid Mobilization in Hanford Sediments under Unsaturated Transient Flow Conditions:  Effect of Irrigation Pattern

Abstract: Colloid transport may facilitate off-site transport of radioactive wastes at the Hanford site, Washington State. In this study, column experiments were conducted to examine the effect of irrigation schedule on releases of in situ colloids from two Hanford sediments during saturated and unsaturated transientflow and its dependence on solution ionic strength, irrigation rate, and sediment texture. Results show that transient flow mobilized more colloids than steady-state flow. The number of short-term hydrologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
96
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 35 publications
15
96
0
Order By: Relevance
“…The exchange of colloids between mobile and immobile zones were likely controlled by slow advection in addition to diffusion. The occurrence of larger quantity of colloids from unsaturated column studies were found in transient flow condition due to movement of colloids present in immobile zone [61,66,89]. All these studies indicated that the colloid can be attached in the immobile zone created by heterogeneity of the medium and by the presence of gaseous phase, which could be remobilized in the large rainfall and infiltration events.…”
Section: Attachment At the Immobile Zonesmentioning
confidence: 93%
“…The exchange of colloids between mobile and immobile zones were likely controlled by slow advection in addition to diffusion. The occurrence of larger quantity of colloids from unsaturated column studies were found in transient flow condition due to movement of colloids present in immobile zone [61,66,89]. All these studies indicated that the colloid can be attached in the immobile zone created by heterogeneity of the medium and by the presence of gaseous phase, which could be remobilized in the large rainfall and infiltration events.…”
Section: Attachment At the Immobile Zonesmentioning
confidence: 93%
“…First, DOM could come from the mobilization of colloids and soil particles containing organic matter. Numerous studies have highlighted the mobilization of colloids and soil particles in soil columns (Laegdsmand et al, 1999;Majdalani et al, 2008;Mohanty et al, 2015;Zhuang et al, 2007) and field studies (Jarvis et al, 1999;Zhang et al, 2016) due to an increasing water velocity. The rise of the water table during storm flow conditions induced an increase in the water pressure and velocity in the soil macroporosity, which could be related to a piston-like effect (Zhao et al, 2017).…”
Section: Conceptual Model For Colloidal-dom Mobilization In Soil Solumentioning
confidence: 99%
“…According to the cleanup plans for the Hanford site, waste tanks are scheduled to be removed and the subsurface matrix will be returned to physical and chemical environments characteristic of natural recharge of dilute pore water at circumneutral pH. In the subsurface environment, the transport of colloids in aqueous suspension is generally believed to be mainly influenced by media water content, fluid flow rate and flow pattern, ionic strength, and pH of the pore water (Kaplan et al, 1993;Roy and Dzombak, 1997;Gamerdinger and Kaplan, 2001;Um and PaPelis, 2002;Ryan and Gschwend, 1994;Zhuang et al, 2007). Therefore, information regarding the stability or remobilization of radionuclide-containing secondary precipitates under changed physicochemical conditions of the background solutions in the future subsurface environment is needed in order to forecast transport and to conduct a long-term safety performance assessment in Hanford site after tank closure.…”
Section: Hanford Sedimentsmentioning
confidence: 99%